Evaluation of Morphological and Mitochondrial Alterations of Mouse Fetus after Exposure to Methyl tert-butyl Ether: Effect of MTBE on Fetus Mouse - Faizi, Mehrdad; Jamal, Fatemeh; Mohammadzadeh Asl, Baharak; Naserzadeh, Parvaneh; Sadabadi, Zeinab; Salimi, Ahmad; Pourahmad, Jalal (Iranian Journal of Pharmaceutical Sciences, 2019)
Although the biokinetics, metabolism, and chemical toxicity of methyl tert-butyl ether are well known, little attention was paid to the potential toxic effects of MTBE on reproduction and development in mammals. To evaluate the effects of MTBE on pregnant animals, two groups (control and test) of NMRI mice were chosen. In test group 500 and 1000 mg/Kg of it were administered intraperitonealy at 11 days of gestation and in control group no injection was made. Caesarean section was performed at 15 days of the gestation, and the fetus and placentas were examined externally. Based on our morphological results, MTBE caused significant increase (p < 0.05) in the weight of fetuses and the weight of placentas, the diameter of placentas and crown-rump length of fetuses. Also, our mitochondrial results showed significant (p < 0.05) increase in mitochondrial swelling, ROS formation and also significant (p < 0.05) decreased in MMP on mitochondria isolated from liver and brain in test group. These results suggest that MTBE through ROS formation may induce the mitochondrial dysfunction which in turn leads to inhibition of angiogenesis and morphological alterations in fetus of mouse.